Socialization Of Black Campaign Prevention On Social Media For Generation Z In Facing The 2024 Election: Sosialisasi Pencegahan Black Campaign di Media Sosial Bagi Generazi Z Dalam Menghadapi Pemilu 2024 - Afriandi, Fadli; Marlizar, Desi; Nabilla Kesha, Cut (Universitas Haji Sumatera Utara, 2025)
General Elections are a pillar of democracy which is the main mechanism in the process of changing power. In the election process, community participation has a significant impact on the process of government legitimacy. Generation Z is one of the people participating in the 2024 elections. Generation Z is a generation of Digital Natives where they grew up in the digital era and are accustomed to using digital technology, one of which is obtaining information and communication on social media. Even though social media is a popular platform, the information provided cannot provide accurate and correct information. This service aims to provide education to students of SMAN 8 Takengon Unggul regarding efforts to prevent black campaigns on social media so that the 2024 Election will be of high quality. This activity uses the socialization method through lectures containing introductory material, potential threats, information verification, and efforts to prevent black campaigns that can be carried out. The results of this service show that there has been a change in students' knowledge in responding to campaign information on social media, which was initially minimal and easy to believe, becoming more selective and verifying the information obtained first. This service activity also has a significant impact on increasing digital literacy and critical thinking in obtaining election-related information.